Bolus gastric feeds improve nutrition delivery to mechanically ventilated pediatric medical patients: Results of the COntinuous vs BOlus multicenter trial. Issue 5 (27th January 2022) - Brown, Ann‐Marie; Irving, Sharon Y.; Pringle, Charlene; Allen, Christine; Brown, Miraides F.; Nett, Sholeen; Singleton, Marcy N.; Mikhailov, Theresa A.; Madsen, Erik; Srinivasan, Vijay; Anthony, Heather; Forbes, Michael L.; et al.
Abstract: Background: Comparison of bolus gastric feeding (BGF) vs continuous gastric feeding (CGF) with respect to timing and delivery of energy and protein in mechanically ventilated (MV) pediatric patients has not been investigated. We hypothesized that bolus delivery would shorten time to goal nutrition and increase the percentage of goal feeds delivered. Methods: Multicenter, prospective, randomized comparative effectiveness trial conducted in seven pediatric intensive care units (PICUs). Eligibility criteria included patients aged 1 month to 12 years who were intubated within 24 h of PICU admission, with expected duration of ventilation at least 48 h, and who were eligible to begin enteral nutrition within 48 h. Exclusion criteria included patients with acute or chronic gastrointestinal pathology or acute surgery. Results: We enrolled 158 MV children between October 2015 and April 2018; 147 patients were included in the analysis (BGF = 72, CGF = 75). Children in the BGF group were slightly older than those in the CGF; otherwise, the two groups had similar demographic characteristics. There was no difference in the percentage of patients in each group who achieved goal feeds. Time to goal feeds was shorter in the BGF group (hazard ratio 1.5 [CI 1.02–2.33]; P = 0.0387). Median percentage of target kilocalories (median kcal 0.78 vs 0.59; P ≤ 0.0001) and median percentage of protein delivered (median protein 0.77 vs 0.59; P ≤ 0.0001) was higher for BGF patients. There was no difference in serial oxygen saturation index between groups. Conclusion: Our study demonstrated shorter time to achieve goal nutrition via BGF compared with CGF in MV pediatric patients. This resulted in increased delivery of target energy and nutrition. Further study is needed in other PICU populations.